AGENDA & MINUTES GOVERNING COUNCIL MEETING OF IAPSM UPUK - Editor, Chief (Indian Journal of Community Health, 2016)
AGENDA & MINUTES GOVERNING COUNCIL MEETING OF IAPSM UPUK Department of Community Medicine, SRMS IMS, Bareilly (15th Oct’ 2016; 03:00 to 04:00 PM)